Training during recessions: Recent European evidence - Marco Bertoni; Giorgio Brunello (IZA Journal of Labor Policy, 2022)
We use European Union Labour Force Survey data for the period 2005-2018 to investigate the cyclicality of training in Europe. Consistent with the view that firms use recessions as times to update skills, we find that training participation is moderately countercyclical for the employed. Within the not-employed group, this is true also for the unemployed, who are likely to be involved in public training programs during recessions, but not for the inactive, who may be affected by liquidity constraints.
Keywords: J24; E32; 330; training; recessions; Europe